Cultivation of the Muslim personality in light of surah al-Khaf : an analytical study - Hamdeh, Basel Munir (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The purpose of this research is to identify the elements of the ideal Muslim personality as portrayed in SËrah al-Kahf and to clarify the unique characteristics and the essentials factors of this personality. This ideal character when it embodies positive constructive elements will be equipped to face all types of contemporary challenges and problems, view the world in light of the guidance in the Qur'Én and Sunnah, and remain steadfast on the principles and values of God. This ideal character will contribute to a positive change in society. This research addressed the aspects that contribute in the making of a personality that is founded on true faith and high standards; those aspects include faith, knowledge, intellectuality, and leadership. The study identified the fundamentals of each of these traits and how they can be cultivated in light of SËrah al-Kahf. The inductive method as well as the analytical method was used to study, compare and categorize the statements and thoughts of the MuffasirÊn (Qur'Én Interpreters) in order to extract effective elements that contribute in cultivating the Muslim character that is established on firm principles. The research suggests that the Muslim character is grounded on true faith and good actions; and that good actions are the fruit of true faith, and that goodness of the individual leads to the goodness of the society. The equation is clear and explicit that whenever the individual is steadfast on his principles, values, and faith, the result will be a better society. This ideal character is steadfast on the true path and takes the proper means to remain firm on truth. In addition, this personality seeks knowledge from people of knowledge and implements the knowledge learned through actions. Much more, this character is distinguished with clear consciousness, thought, and clear vision of the reality of the world and its occurrences. The research shows the role of reflection in the verses of Qur'Én , especially the parables mentioned SËrah al-Khaf in building a conscious intellectual personality and its effect on Muslim behavior with himself and others. The verses of SËrah al-Kahf, especially the stories in it, refer to the practical methods that if implemented will cultivate an ideal Muslim character composed all the elements mentioned. Similar to how faith is tied to knowledge, knowledge is tied to strength and empowerment. The continuity and connection between the themes mentioned in the stories of SËrah al-Kahf is evident: 1) Faith, mentioned in the story of the companions of cave. 2) Wealth aiding in knowledge the story of the two gardens. 3) Knowledge aiding in strength and empowerment, mentioned in the story of Moses and Khadr. 4) Lastly, once intentions are purified, all of these things are crowned with leadership and empowerment as was exemplified in the story of Dhū al-Qarnayn.